A prospective follow up of age related changes in the subchondral bone density of the talus of healthy Labrador Retrievers. Issue 1 (December 2016) - Dingemanse, W.; Müller-Gerbl, M.; Jonkers, I.; Sloten, J.; van Bree, H.; Gielen, I.
Abstract Background During growth, the skeletal structures adapt to the increased loading conditions and mature to a fully-grown skeleton. Subchondral bone density reflects the effect of long-term joint loading and it is expected to change over time. The aim of this study was to describe the long-term changes in the density distribution of the subchondral bone of the talus of healthy Labrador Retrievers in a prospective study. Results The subchondral bone density distribution was evaluated using computed tomographic osteoabsorptiometry (CTOAM). Visually, all joints showed very similar density distribution patterns. No significant differences in the topography of the density maxima were found between t1 and t2 . The mean density, maximum density, and maximum area ratio (MAR) were significantly increased with increasing age. Conclusions The subchondral bone density of the talus of healthy Labrador Retrievers increases with increasing age. It is likely an adaptive response of the subchondral bone due to increased joint loading during growth.